Adverse selection and heterogeneity of demand responsiveness - Normann Lorenz (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
This paper analyzes the distortions of (health) insurers' benefit levels due to adverse selection if individuals' responsiveness to differences in contracts is heterogeneous. Within a discrete choice model with two risk types and imperfect competition the following results are shown: In the pooling equilibrium, a positive correlation of low risk and high responsiveness (e.g., younger individuals being both healthier and faster to switch insurers than older individuals) increases the distortion of the uniform benefit level if the share of low risks is small; if the share of low risks is large, the reverse holds, but only if the average level of responsiveness is high. In the separating equilibrium, a positive correlation increases the distortion of the contract for the low risks, unless the number of insurers offering the contract for the high risks is very small or a large share of the high risks chooses the contract designated for the low risks. These results imply that the welfare effects of a policy intervention of making individuals more responsive crucially depend on which risk types' responsiveness is increased more. The results also have implications for the estimation of the level of risk aversion and of the welfare effects of adverse selection.
Keywords: I13; 330; adverse selection; discrete choice